An unusual case of severe left ventricle outflow tract obstruction due to a coexistence of Takotsubo cardiomyopathy with septal hypertrophic cardiomyopathy - Parato, Vito Maurizio; Gizzi, Germana; D'Agostino, Simone; Pelliccioni, Simona; Scarano, Michele (Monaldi Archives for Chest Disease, 2021)
Hypertrophic cardiomyopathy (HCM) is a genetic disorder presenting with a pathological increase of left ventricle (LV) wall thicknesses. The most frequent morphological form is characterized by an abnormal LV basal septal hypertrophy. Tako-Tsubo cardiomyopathy (TTC) is a transient left ventricular systolic dysfunction induced by high physical or emotional stress. Its occurrence with HCM is unusual. However, this presentation occurs more often with the classic asymmetrical septal hypertrophy compared with the apical variant. This case demonstrates that the coexistence of TTC with septal HCM in an elderly patient may lead to a severe hemodinamic instability picture.